2018
DOI: 10.1002/etc.4223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of passive sampling polymers and nonequilibrium adjustment methods in a multiyear surveillance of sediment porewater PCBs

Abstract: Polymeric passive sampling devices are increasingly used to measure low-level, freely dissolved concentrations of hydrophobic organic contaminants in environmental waters. A range of polymers have been used for this purpose, and several different methods of accounting for nonequilibrium using performance reference compounds (PRCs) have been proposed. The present study explores the practical impacts of these decisions in an applied context using results from a multiyear passive sampling surveillance of polychlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In the 5‐ to 7.5‐cm depth interval, significant reductions in Σ C pw were only observed in plot A, where they were significant at all sampling events ( t test, p < 0.05). This finding is discussed at greater length separately (Sanders et al ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In the 5‐ to 7.5‐cm depth interval, significant reductions in Σ C pw were only observed in plot A, where they were significant at all sampling events ( t test, p < 0.05). This finding is discussed at greater length separately (Sanders et al ).…”
Section: Resultsmentioning
confidence: 86%
“…Each K d value is calculated from an average concentration in sediment ( C sed ) value ( n = 5) for the 0‐ to 5‐cm horizon and an average adjusted porewater concentration ( C pw ′) value ( n = 5) for the 0‐ to 2.5‐cm horizon. The C pw value was adjusted with the k e – K ps performance reference compound method (Sanders et al ). Orange line: organic carbon model; black line: organic carbon and black carbon model (see text for descriptions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the use of PRCs contributes to the uncertainty of estimating C free , especially for poorly equilibrated PRCs (Jonker et al, 2018, 2020; Joyce et al, 2020). Uncertainty associated with the use of poorly equilibrated PRCs (see Jalalizadeh & Ghosh, 2017; Sanders et al, 2018) may have contributed to the higher interlaboratory variability for the more hydrophobic compounds we observed. When selecting polymer sampler deployment methods, those that result in higher fractional loss of PRCs and a closer approach to equilibrium have been shown to result in lower uncertainty (i.e., higher accuracy; Jalalizadeh & Ghosh, 2017) and should be employed whenever feasible.…”
Section: Resultsmentioning
confidence: 87%
“…In contrast to laboratory, or ex situ, deployments where conditions can be controlled to favor achieving equilibrium, PRCs are of particular value in field deployments of passive samplers (i.e., in situ), where equilibrium cannot be assumed or determined. Several studies have used PRCs in water column and sediment in situ deployments to estimate C free (Smedes 2007; Tomaszewski and Luthy 2008; Fernandez et al 2009, 2012; Perron et al 2013a, 2013b; Estoppey et al 2014; Burgess et al 2015; Joyce et al 2015; Apell and Gschwend 2016; Apell et al 2018; Sanders et al 2018). In a previous study, we suggested that using a sampling rate approach (Booij and Smedes 2010) or a diffusion‐based approach (Thompson et al 2015) to determine C free often resulted in statistically indistinguishable results in a field deployment (Joyce and Burgess 2018).…”
Section: Introductionmentioning
confidence: 99%